Bharat ka Samvidhan, Vrittik Acharniti aur Manav Adhikar. - Mellalli, Praveen kumar (SAGE Publications India, 2017)
Written as per the latest Visvesvaraya Technological University (VTU)-prescribed syllabus (for B.E./B. Tech. I & II semesters), Constitution of India, Professional Ethics and Human Rights provides a comprehensive overview of the Constitution of India, the basics of human rights and practice of professional ethics. This textbook aids easy understanding and helps in successfully achieving the objectives and outcomes of this course in the most efficient and effective manner. Key Features Full coverage of the 2015-2016 syllabus Topics based on recent updates Logically sequenced chapters aiding eas.